PERAN PENGEMBANGAN DAN PEMANFAATAN TEKNOLOGI PENDIDIKAN DAN PEMBELAJARAN DALAM MENINGKATKAN KUALITAS MENGAJAR - Khozin, Alfina Nur Mu’azizah; Shofiatul Mar'ah; Shofiatun Umairoh; Alfia Rohmatus Sa'adah; Lailatul Farikha Miftahus S. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Along with the times, technology in its development certainly brings changes to life, especially in the world of education which will also continue to experience development. This study aims to determine the role of educational technology in improving the quality of education in an era full of progress. The approach in this study uses the literature review method (library research), where researchers collect materials related to research from books, journals, scientific articles. The results of this study can be explained that the role of educational technology in improving the quality of education includes 1) providing learning facilities through the process of planning, developing, utilizing, managing and evaluating learning resources; 2) solving existing learning problems and being studied thoroughly by integrating various scientific disciplines in an integrated manner; 3) utilizing technology that can make twork effective and efficient, both as a product and process to solve learning problems; 4) providing alternatives to solving the performance problems of educational organizations by structured using performance and instructional design; 5) can give birth to new innovations in the field of education and teaching in order to solve existing problems.